(untitled) (The Conference Hub, 2025)
Small business and private entrepreneurship are one of the main elements of every economic system, and their development makes a significant contribution to socio-economic stability, job creation, and innovation processes. However, small businesses need various financial resources to successfully implement their activities. Thus, commercial banks play an important role in microfinancing small businesses. Microfinancing provides small businesses with the opportunity to obtain the necessary funds, which helps them grow and increase their competitiveness.